Efektivitas Edukasi Kesehatan dalam Meningkatkan Pengetahuan Keluarga Pasien tentang Manajemen Nyeri Pascaoperasi - Latifah, Latifah; Peristiowati, Yuly (Yayasan Inspirasi El Burhani, 2026)
Introduction: Postoperative pain management is a crucial aspect of nursing care that directly influences patient comfort and recovery outcomes. Effective pain control requires not only clinical intervention but also family involvement, as families assist in daily care and monitoring patient conditions. However, limited family knowledge regarding pain management often creates barriers to optimal recovery and increases the risk of postoperative complications. Objective: This community service activity aimed to improve family knowledge of postoperative pain management at Setio Husodo General Hospital, Kisaran, and to strengthen family participation in supporting the patient recovery process. Method: The activity was conducted on October 9, 2025, involving ten family members of postoperative patients. An educational and participatory approach was applied through health education sessions, interactive discussions, and direct demonstrations using leaflets. Educational materials included an explanation of postoperative pain, recognition of pain symptoms, pharmacological and non-pharmacological pain management strategies, and the role of families in patient care. Knowledge levels were assessed through pre-test and post-test questionnaires. The data were analyzed descriptively by comparing the average knowledge scores before and after the intervention. Result: The results demonstrated a significant improvement in family knowledge. The average knowledge score increased from 54.8 before the intervention to 69.2 after the education sessions. Participants showed better understanding in identifying pain symptoms and applying non-pharmacological pain management techniques such as relaxation, distraction, and proper positioning. Active engagement during discussions reflected increased awareness of the importance of family involvement in postoperative care. Conclusion: Health education effectively improved family knowledge regarding postoperative pain management at Setio Husodo General Hospital, Kisaran. This program is expected to become a sustainable initiative to enhance family engagement and improve the quality of nursing services.